Epidemiology, Prevalence and Preventive Guidelines of Hepatitis B Virus Infection (Journal of Medical & Health Sciences Review, 2025)
This study aims to determine the incidence of hepatitis B infection in the District Multan region while also focusing on risk factors and epidemiology, which are the primary causes of HBV infection. Individuals whom ages are between 18-50 are included in data sampling. Individuals whom having history of any hepatitis infection or having any chronic illness involved in exclusion criteria. By taking ethical approval and informed consent from individuals summarized data like medical history, behavioral pattern and recent travel to high frequency rate areas is gathered. To inquire about HBsAg blood sample is collected, synthesized and examined by using serologic methods. Further analysis is done on participants whom are tested positive for HBV using diagnostic techniques. The findings of this research is support in understanding the roots of HBV and linked risk factors and help us in reaching insights to take preventive steps for curing HBV and further which strategies are to be taken in future.